Development of Snake and Ladders Learning Media for the Introduction and Management of Basic Emotions in Children Aged 2â€“4 Years - Christine Dewiyani; Imamah Imamah; Sukiman Sukiman (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research aimed to develop and test the feasibility of snakes and ladders learning media to help children aged 2â€“4 years recognize and manage basic emotions at SPS Negeri Bale Bermain Cendkia Kemayoran. Using the Four-D model (Define, Design, Develop, Disseminate), the define stage found that 75% of children struggled to identify emotions, 80% lacked adaptive management strategies, and 70% could not express emotions proportionally. In the design stage, a jumbo floor game (200x200 cm) with supporting components was created. At the develop stage, validation by three experts (subject, media, and early childhood practitioner) scored 97.67/120 (81.39%), categorized as â€œValid.â€ Limited trials with 30 children showed average pre-test scores of 30.33 (42%) and post-test scores of 49.07 (68%), reflecting a 26% increase and a gain score of 0.45 (â€œLowâ€). The highest improvement appeared in emotion recognition with a gain score of 0.54 (â€œMediumâ€). In the disseminate stage, socialization and implementation assistance were conducted across early childhood institutions in Kemayoran District. Overall, this research produced valid and effective snakes and ladders media, proven to support children in recognizing and managing basic emotions through fun, interactive play.